Cetuximab in non-small-cell lung cancer. Issue 2 (February 2012) - Carillio, Guido; Montanino, Agnese; Costanzo, Raffaele; Sandomenico, Claudia; Piccirillo, Maria Carmela; Di Maio, Massimo; Daniele, Gennaro; Giordano, Pasqualina; Bryce, Jane; Normanno, Nicola; Rocco, Gaetano; Perrone, Francesco; et al.
Cetuximab is a chimeric human–mouse anti-EGF receptor monoclonal antibody. In Phase I studies, no dose-limiting toxicities were observed with cetuximab as a single agent or combined with chemotherapy; pharmacokinetic and pharmacodynamic analyses supported 250 mg/m 2 weekly administration. Skin toxicity, diarrhea and fatigue were the most common toxicities. The positive results obtained in Phase II trials in patients with advanced non-small-cell lung cancer prompted two randomized Phase III trials evaluating cetuximab in addition to first-line chemotherapy. Both trials showed a small benefit in overall survival for the experimental treatment, which was considered insufficient by the EMA for marketing approval. However, a subgroup analysis of the FLEX Phase III trial recently demonstrated a larger survival benefit from the experimental treatment in patients with high immunohistochemical EGF receptor expression. This finding, if confirmed prospectively, could represent a new opportunity for positioning cetuximab into the standard treatment of advanced non-small-cell lung carcinoma.